Metode Dakwah Terhadap Mahasiswa Di Forum Kajian Dakwah IAI AL-AZIS - Andini Fitriah; Muhammad N Abdurrazaq; Sobirin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
A college student is a learner listed and runs his/her education in college either academy, polytechnic, college, institute, or university. A student needs to have high intellectuality and mature thinking intelligence, and determining their on personality so that they can protect themselves from the entrance of irrelevant teaching or understanding with religion values. Therefore the researcher discusses the implementation of the right da’wah method with its mad’u classification who is college student. The purpose of this research was to find out and to understand how the da’wah methods used towards the students in Da’wah Study Forum of IAI AL-AZIS and What are the supporting factors and inhibiting factors in conveying da’wah method in Da’wah Study Forum at IAI AL-AZIS. This research used qualitative research in the form of observation. The techniques of data collection were open interview and documentation. This result shows that the right da’wah method used on students is question and answer and discussion. The supporting factors are such as the fulfillment of da’wah component in this study activity, for the inhibition factor is limited time either from the speakers as da’i or the students as the mad’u. This causes the study on Thursday is not efficient yet because of the limited time. However it is still temporary because the structures of Da’wah Study Forum will keep trying to maximize the time so that the study activity can run according to the schedule which had been made.